Delay in Space: Orbital Angular Momentum Beams Transmitting and Receiving in Radio Frequency. Issue 7 (2nd October 2016) - Liu, Baiyang; Cui, Yuehui; Li, Ronglin
ABSTRACT: Using an orbital angular momentum-based communication system to increase the channel capacity has recently attracted more and more attention. This article proposes a novel antenna array to transmit and receive orbital angular momentum beams at a radio frequency (3 GHz) by using delay in space. Different from the well-known uniform circular array which needs a phase-shifting network, every element in the proposed helicoidal array has the same phase. As long there are enough array elements and a power divider, arbitrary orbital angular momentum mode can be generated easily by only changing the positions of the array elements without any phase-shifting. In this experiment, l = 1 and l = 2 helicoidal arrays with eight half-wavelength dipoles are fabricated. The simulated and measured results, such as S parameters, near-field orbital angular momentum properties, far-field orbital angular momentum properties, the channel isolation between different orbital angular momentum channel, and the packet-loss-rate of an orbital angular momentum-based communication system using the helicoidal arrays, are presented, which shows that a helicoidal array can indeed generate arbitrary orbital angular momentum mode. Moreover, different kinds of antenna arrays can be constructed using delay in space and delay in phase together. The authors propose a crossed array to generate orbital angular momentum beams in four directions. The simulation and experimental results of the crossed array are demonstrated. Delay in space is another degree of freedom to generate orbital angular momentum beams in radio frequency.